2021
DOI: 10.1098/rsos.201087
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and anticorrosion properties of polyurethane coatings derived from recycled polyethylene terephthalate and palm olein-based polyols

Abstract: Polyols of palm olein/polyethylene terephthalate (PET) were synthesized by means of incorporating recycled PET from waste drinking bottles in different proportions into palm olein alkyd in the presence of ethylene glycol. The polyols were characterized by FTIR, and theirs hydroxyl value (OHV), acid value (AV) and viscosity were determined. The formulation of the polyurethane coating was carried out by dissolving the polyol in mixed solvent of cyclohexanone/tetrahydrofuran (THF) (4 : 1) followed by reacting 1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Thermoplastic PU topcoats, the most abundantly employed coating systems, have been known to provide excellent environmental shielding, smoother surface finish, and scratch and corrosion resistance. , Their tough, rubbery nature allows them to avoid plastic deformation during impact and erosion tests. Adamu et al reported higher thermal stability and anticorrosion characteristics when traditional PU coatings were blended with PET . Modified urethane resins have also been studied for environmental protection of radomes .…”
Section: Resultsmentioning
confidence: 99%
“…Thermoplastic PU topcoats, the most abundantly employed coating systems, have been known to provide excellent environmental shielding, smoother surface finish, and scratch and corrosion resistance. , Their tough, rubbery nature allows them to avoid plastic deformation during impact and erosion tests. Adamu et al reported higher thermal stability and anticorrosion characteristics when traditional PU coatings were blended with PET . Modified urethane resins have also been studied for environmental protection of radomes .…”
Section: Resultsmentioning
confidence: 99%
“…Although they cannot be considered as bio-based materials, environmentally friendly PU coatings have been also prepared by using wastes as a source for the polyol synthesis. [77,78] In this regard, it is worth mentioning the work by Adamu et al, who synthesized polyols incorporating up to 15% of recycled PET from waste drinking bottles into palm olein alkyd in the presence of ethylene glycol. [77] The resulting PU coatings, obtained by reacting the PET-containing polyol with methylene diphenyldiisocyanate in the presence of a tin catalyst, showed improved corrosion protection ability.…”
Section: Bio-based Coatingsmentioning
confidence: 99%
“…These triglycerides were the main components used during the polymerization of the coconut oil and formed into polyurethane-based coating [7]. PU-based coatings according to Abbas et.al, that it displays good thermal and anticorrosion properties in which the decrease of Icorr and an increase of the Ecorr revealed that it exhibits corrosion protection ability [8]. However, PU coatings are polymers if exposed to ultraviolet radiation cause breakage of the chemical bonds in the material, thus a reduction of its molecular weight and loss in it mechanical features known as photo-oxidative degradation [9].…”
Section: Introductionmentioning
confidence: 99%